(untitled) (Gestão & Regionalidade, 2022)
Socio-environmental sustainability is increased to the strategic plan of companies when they understand the need to balance the use of natural resources, provide quality of life to the community and profits. The objective of the research was to verify the perspectives of the interested parties on the socio-environmental sustainability actions of a credit cooperative agency, located in the Germanic Valley, in Rio Grande do Sul. A descriptive, qualitative and quantitative case study was carried out. The data were collected through an interview with the person responsible for the socio-environmental sustainability sector and through the application of questionnaires to 44 members, 8 employees and a director of the credit union. The main results show that socio-environmental sustainability is a cooperative strategy. There are social initiatives with results perceived by the interested parties. However, environmental actions at a bank branch are challenging and need more attention.